L'UE déclare que le cycle de Doha est favorable au développement - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
S'exprimant au Brésil le 30 janvier 2003, le Commissaire...